Curcumin Ingestion Inhibits Mastocytosis and Suppresses Intestinal Anaphylaxis in a Murine Model of Food Allergy. - Shannon R M Kinney; Logan Carlson; Jennifer Ser-Dolansky; Chelsea Thompson; Sagar Shah; Amos Gambrah; Wei Xing; Sallie S Schneider; Clinton B Mathias (PLoS ONE, 2015)
IgE antibodies and mast cells play critical roles in the establishment of allergic responses to food antigens. Curcumin, the active ingredient of the curry spice turmeric, has anti-inflammatory properties, and thus may have the capacity to regulate Th2 cells and mucosal mast cell function during allergic responses. We assessed whether curcumin ingestion during oral allergen exposure can modulate the development of food allergy using a murine model of ovalbumin (OVA)-induced intestinal anaphylaxis. Herein, we demonstrate that frequent ingestion of curcumin during oral OVA exposure inhibits the development of mastocytosis and intestinal anaphylaxis in OVA-challenged allergic mice. Intragastric (i.g.) exposure to OVA in sensitized BALB/c mice induced a robust IgE-mediated response accompanied by enhanced OVA-IgE levels, intestinal mastocytosis, elevated serum mMCP-1, and acute diarrhea. In contrast, mice exposed to oral curcumin throughout the experimental regimen appeared to be normal and did not exhibit intense allergic diarrhea or a significant enhancement of OVA-IgE and intestinal mast cell expansion and activation. Furthermore, allergic diarrhea, mast cell activation and expansion, and Th2 responses were also suppressed in mice exposed to curcumin during the OVA-challenge phase alone, despite the presence of elevated levels of OVA-IgE, suggesting that curcumin may have a direct suppressive effect on intestinal mast cell activation and reverse food allergy symptoms in allergen-sensitized individuals. This was confirmed by observations that curcumin attenuated the expansion of both adoptively transferred bone marrow-derived mast cells (BMMCs), and inhibited their survival and activation during cell culture. Finally, the suppression of intestinal anaphylaxis by curcumin was directly linked with the inhibition of NF-κB activation in curcumin-treated allergic mice, and curcumin inhibited the phosphorylation of the p65 subunit of NF-κB in BMMCs. In summary, our data demonstrates a protective role for curcumin during allergic responses to food antigens, suggesting that frequent ingestion of this spice may modulate the outcome of disease in susceptible individuals.